Wind Energy Assessment in Auchi, Nigeria using Weibull Distribution and NASA Data - Seidu, I.; Salisu, S.; Masud, A. A.; Musa, U.; Almustapha, D. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The advancements in wind energy farms in the developed world have significantly reduced the cost of wind energy turbine systems, making them more competitive and contributing to a reduction in global warming, which has a widespread impact on the global population. This study evaluates the wind energy potential of Auchi, a community in Edo State, Nigeria, using the Weibull distribution function. Wind speed data from NASA spanning an 11-year period (2012-2022) at a height of 10 m is utilized, and statistical methods are employed to estimate the Weibull parameters (scale and shape), which are then used to calculate the wind power density and the probability density function which was validated using root mean square error (RMSE) and coefficient of determination R2. The results indicate that Auchi possesses favorable wind conditions for power generation, with an average wind speed of 6.07 m/s and an average power density of 153.64 W/m². Additionally, the study examines the influence of surface roughness and height on wind speed and power density, highlighting the potential for harnessing wind energy for electrification purposes in Auchi, thereby offering a solution to Nigeria’s energy challenges.